A Study of Polar Ozone Depletion in the Lower Stratosphere. -Dynamical assimilation of O3 and N2O data from Odin/SMR and ENVISAT/MIPAS - RÖSEVALL, JOHN (2006)
For more than 20 years, a hole in the ozone layer has formed each spring over Antarctica when sunlight returns to the polar region. Similar albeit far less extensive ozone destruction has also been observed in the Arctic polar vortex after colder than average winters. Since the Arctic polar vortex is less stable and therefore warmer than its southern counterpart, total depletion of ozone has however not occurred in the northern hemisphere .To quantify the depletion of polar ozone it is necessary to somehow follow air-masses in the stratosphere so their ozone concentrations can be measured at consecutive times. The objective of this thesis is to demonstrate how polar ozone depletion can be mapped and quantified by assimilating ozone data from satellites into an off-line wind driven non-dispersive transport model. With access to a large set of satellite data, assimilated fields can be built up that are far less noisy than the individual satellite ozone profiles. The transported fields can subsequently be compared to later sets of incoming satellite data so that the rates and geographical distribution of ozone depletion can be determined. To accomplish this strategy a low-diffusive transport and assimilation model DIAMOND, (Dynamical Isentropic Assimilation Model for OdiN Data) has been developed. It has been used to study Antarctic as well as Arctic polar ozone destruction by assimilating ozone profiles from the ENVISAT/MIPAS and Odin/SMR satellite-instruments. Nitrous oxide profiles from Odin/SMR have furthermore been assimilated in parallel with the ozone data for the purpose of tracing horizontal and vertical movements in the polar vortex.